Pemberdayaan Masyarakat Berbasis Masjid: - Balqis Mawaddah Lubis; Ade Izmi Ningtyas; Dini Lestari Hasibuan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
This study aims to determine the management of the mosque, namely, the Al-Ikhlas Mosque which is located on Jl. Harmonika Setia Budi Pasar II Graha Tanjung Sari, Medan, North Sumatra. As one of the productive mosques in empowering the community. Where the management of this mosque is held by the Mosque Prosperity Board. And the type of research used is qualitative research through a descriptive approach. And from the research conducted, it shows that the empowerment managed at the Al-Ikhlas mosque is going well even though it is not optimal. Keywords: mosque-based, community empowerment